The Impact of Social Activities, Management Strategies, and Human Capital on Improving Company Financial Performance - Aviyanti, Richo; Fatmala, Indra; Putri, Nanda (Politeknik Negeri Madiun, 2024)
The selection of management strategies is a fundamental factor in improving financial performance. Improved financial performance will have an impact on business sustainability. This research aims to understand and analyze the effect of social activities, management strategies, and human capital on the financial performance of companies listed in the IDX80 index for the period 2020-2022. This research uses a quantitative approach with a positivist paradigm. The population of this study is all companies included in the IDX80 category for the 2020-2022 period, totaling 80 companies. The sample was selected using purposive sampling, resulting in a sample of 47 companies with 141 observations (N). Data were analyzed using multiple linear regression analysis with SPSS tools. The result of this study indicates that human capital can enhance the financial performance of IDX80 companies. However, Information on social activities does not improve financial performance because social activities increase operational costs. Management strategies do not significantly affect financial performance due to the high cost associated with complex and comprehensive management strategies, which may disrupt financial performance. Companies are recommended to commit to managing human capital to create unique, rare, and irreplaceable intangible assets. The uniqueness of a company will add value, impacting financial performance stability. This research focuses on companies with a similar or equivalent focus on competitive advantage. Expanding the scope will enhance the generalizability of research results.